The Implications of the COVID-19 Pandemic on Trade. (1st June 2020) - CARREÑO, Ignacio; DOLLE, Tobias; MEDINA, Lourdes; BRANDENBURGER, Moritz
Abstract : On 17 March 2020, the President of the European Council, Charles Michel, and the President of the European Commission (hereinafter, Commission), Ursula von der Leyen, announced further European Union (EU) actions in response to the COVID-19 outbreak. Since the pandemic reached Europe, the EU has adopted a number of trade-related measures, including the issuance of guidelines for national border management, as well as export authorisation requirements. On 14 March 2020, the Commission adopted "Commission Implementing Regulation (EU) 2020/402 of 14 March 2020 making the exportation of certain products subject to the production of an export authorisation", temporarily restricting exports of "personal protective equipment" to destinations outside of the EU. On 14 April 2020, the Commission announced that it would narrow down export authorisation requirements to protective masks only and extend the geographical and humanitarian exemptions. Governments around the world have been implementing trade-related measures in response to the COVID-19 pandemic, some trade restrictive, but a number of countries have also called for the elimination of export controls and restrictions on essential goods. As the greater implications of the COVID-19 pandemic on trade are still difficult to assess, the emergency measures taken by affected countries already require legal scrutiny. At the same time, it must be noted that, as noted above for the EU measures, measures around the world are subject to change dynamically in view of the evolution of the pandemic.